Estudio taxonómico del género Dyschoriste (acanthaceae) en la Argentina - Ezcurra, Cecilia (2014)
Dyschoriste is a genus of worldwide distribution in warm regions, with two important diversity centers in America, one in southern North America and the other in subtropical South America. This work aims to analyze the taxonomy of the six species of Dyschoriste present in Argentina. The species are delimited, their nomenclature and synonymies are resolved based on the study of type material, they are described and illustrated, and a key to differentiate them is presented. The work includes observations on morphology, nomenclature, typification, distribution, phenology and habitat of the species, and references to representative specimens. A lectotype is designated for Dyschoriste humilis and a neotype for D. niederleinii.